Development Strategies For Improvement Tourists In Ergendang Cave - Hidayah, Nurul; Dewi Shinta Wulandari Lubis (Jurnal Ekonomi, 2024)
Goa Ergendang tourist attraction is a natural wiosata object that has great attractiveness and potential, but in developing this object there needs to be a promotional strategy carried out by the manager to introduce the attraction so that tourists are interested in visiting Goa Ergendang tourist attraction. Data collection used in this research is observation, documentation, literature study and interviews. The research method used is a qualitative method with a descriptive approach. This study aims to determine and analyze the development strategy in increasing tourists at Ergendang Cave. The results of the research show that there are several things that become obstacles in increasing the number of tourists in Ergendang Cave, namely 1. inadequate facilities, smallest location and inadequate accessibility. For strategies that must be carried out in the future are, 1. Promotion and branding, 2. Analyzing the characteristics of potential tourists, affordable tariffs and increasing and collaborating with local communities, 3.